(untitled) (Research, Society and Development, 2021)
Following nasal fractures, zygomatic fractures (ZF) are the second most prevalent of maxillofacial fractures. Isolated fractures of the zygomatic arch (IZAF) are rare, corresponding to less than 10% of all fractures involving the zygomatic-maxillary complex (ZMC). The choice of treatment for IZAF is controversial, and there is no defined consensus in the literature. We seek to evaluate the advantages of closed reductions with minimal accesses over open reductions through a case series and a 10-year literature review. All patients in our study obtained a satisfactory final result in terms of aesthetics and function of the zygomatic arch, with no complications involved. There are criteria established in the current literature on the indication of open surgery or closed reduction. Open reduction with rigid fixation has the most significant number of studies proving its clinical efficacy. However, closed reduction with minimal accesses has proven to be a suitable therapeutic option for IZAF, presenting satisfactory aesthetic results and fewer surgical risks.